Data Encryption Using a Combination of 32-bit MAGENTA Method and Bit Rotation Technique for SQL Database Record Security - Marwa Halim; Tomy Satria Alasi; Sukiman; Wilianto (STMIK Methodist Binjai, 2026)
The rapid growth of digital information systems has increased the vulnerability of sensitive data stored in SQL databases against various security threats, including unauthorized access, data theft, and manipulation. This study aims to enhance the security of SQL database records by developing a hybrid encryption method that combines the modified 32-bit MAGENTA algorithm with the Bit Rotation technique. The proposed method converts every four characters of plaintext into a 32-bit binary representation before applying the modified MAGENTA encryption process, followed by a 4-bit left rotation to increase diffusion and ciphertext complexity. Experimental testing was conducted on student grade records consisting of NIM, course code, and grade fields. The results demonstrate that the combination of 32-bit MAGENTA and Bit Rotation produces highly randomized ciphertext that is difficult to analyze. The decryption process successfully restores the original data without any information loss. Performance evaluation shows that the proposed method maintains the original data length and supports the full ASCII character range (0–255) with acceptable processing time. This hybrid approach provides a stronger security level compared to the use of a single encryption method, making it a promising solution for protecting sensitive records in SQL databases.